Deforestasi dan Krisis Ekologis Kalimantan: Dampak Regulasi Pembukaan Lahan terhadap Kesejahteraan dan Konflik Sosial Masyarakat - Raha Bahari; Mu’adil Faizin (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This study discusses the ecological crisis caused by deforestation in Kalimantan, which stems from land ownership inequality and the way the state manages agrarian resources. Using qualitative and documentary methods through regulatory studies, environmental reports, academic journals, and visual data such as photographs and forest cover maps, this study explores how land clearing policies encourage deforestation and change the social life of communities. The results show that lax regulations and investment orientation give companies considerable leeway to clear land, resulting in land management practices that resemble the domein verklaring system, which is inconsistent with the principle of State Control Rights in the Basic Agrarian Law (UUPA). Land use changes then trigger biodiversity loss, ecosystem damage, and a reduction in the living space of local communities. Conflicts between communities and companies also increase due to unclear land rights and weak state protection, further weakening the position of communities. This study emphasizes that land ownership inequality can continue to recur and exacerbate environmental damage, necessitating more equitable agrarian policies that favor communities and align with the principles of environmental sustainability.